The influence of technological factors on the properties of basalt fiber when used in the manufacture of flexible heat and sound insulating products - Berdnyk, Oksana (Proceedings of the 3rd Annual Conference “Technology transfer: fundamental principle and innovative technical solutions”. Tallin, Estonia, 2019)
Analysis of energy efficiency and operational safety of technological equipment of industrial enterprises, engineering networks, buildings and structures, building structures in many sectors of the economy, including the housing and industrial sectors, causes interest in the use of high-tech, environmentally friendly heat and sound insulation materials with enhanced performance properties. One of the relevant representatives of these materials is basalt fibers and their use as raw materials in the production of flexible heat and sound insulating products. It is known that the chemical composition of the initial melt equally affects the physicochemical and mechanical properties of basalt fibers. The main influence factors, including the chemical composition, are the thermal past of the melt, the method for producing basalt fiber and the conditions for the formation of its structure. These factors determine the structural characteristics of the fiber and, as a consequence, its physicochemical characteristics. The degree of fiber strength is directly determined by its chemical composition and production method. The greatest strength of the fiber is obtained by ensuring the perfect fiber structure in the absence of ruptures of siliceous chains
Keywords: microporous basalt fiber; modification; basalt melt; low-temperature basalt melt